A STUDY ON COMMUNITY MANAGED DEGRADED FOREST IN SRIKAKULAM AND VIZAYNAGARAM DISTRICTS OF ANDHRA PRADESH: Life Science-Environmental sciences - CH. BHAVANNARAYANA; RAO, P. BRAHMAJI; V.SARITHA; K. SARALA (International Journal of Life Science and Pharma Research, 2012)
Ecological study and the impact of Joint Forest Management (JFM) works in the degraded forests of Burna, Baliagam reserve forest areas at Srikakulam and Shikargangii RF at Vizaynagaram districts of Andhra Pradesh were studied. Among them 24 different species recorded at Burna RF and 11 at Baliagam RF and 14 at Shikargangii RF areas. Terminalia tomentosa, Bridella retusa and Casearia elliptica, Pterocarpus uniformly distributed over entire area (100% frequency) at Burna RF. Among 24 tree species recorded at Burna RF, Terminalia tomentosa is uniformly distributed over entire area (100% frequency) followed by Bridella retusa (80%), Casearia elliptica (80%). Though concentrated in some particular area only, Wrightia tinctoria (4.8) recorded higher density value, higher abundance (8) value and higher relative density (20.8). Bridella retusa (1.00) recorded higher relative abundance value followed by Pterocarpus morsupium (0.82). A total of 11 different tree species were observed. 8 species occupied entire area and only three species i.e. Emblica officianalis, Osyris peltata and Xymenia Americana found only in one quadrate with single digit number. Diospyros sylvatica (12.66) and Cleistanthus collinus (4.33) found to be having more density and abundance value. Diospyros sylvatica (43.18) and Cleistanthus collinus (14.77) found to have higher relative density value. Three species namely Emblica officianalis, Osyris peltata and Xymenia Americana (Billa) are having lesser value. Diospyros sylvatica (Gatha) (23.12) and Pterocarpus marsupium (Yegisa) (15.75) found to be having more relative dominance value. Diospyros sylvatica (Gatha) (77.42) and Wrightia tinctoria (Ankudu) (35.61) found to have high IVI value. Shannon’s index of diversity (H) is all most equal in all the areas and Mallavaram RF showed high Simpson’s index of species dominance (C) value and Gedhada and Pothavaram RF areas recorded high Menhinick’s index of Species richness (R). Above all height and girth of all the species also recorded. Annual increment data also recorded and both in treatment and control plot and found that JFM works found to be effective in improving the growth and regeneration of the forests. Our study of TP-1 areas helped to identify endemic and endangered species in the miscellaneous forests. Based on this, measures can be taken up to protect the biodiversity.